Interplay of Purcell effect and extraction efficiency in CsPbBr₃ quantum dots coupled to Mie resonators - He, Ruihua (2023)
Inorganic halide perovskite quantum dots have risen in recent years as efficient active materials in numerous optoelectronic applications ranging from solar cells to light-emitting diodes and lasers, and have lately been tested as quantum emitters. Perovskite quantum dots are often coupled to photonic structures either to enhance their emission properties, by accelerating their emission rate thanks to the Purcell effect, or to increase light extraction. From a theoretical point of view, the first effect is often considered at the single-dipole level while the latter is often treated at the mesoscopic level, except possibly for quantum emitters. In this work we employ a layer of perovskite quantum dots coupled to dielectric Mie resonators to exploit both effects simultaneously and achieve an 18-fold increase in luminescence. Our numerical simulations, combined with spatially- and time-resolved photoluminescence measurements, reveal how the macroscopic response of the perovskite-on-Mie resonator structure results from the interplay of the two effects averaged over the whole spatial distribution of emitters. Our work provides thus guiding principles for maximizing the output intensity of quantum emitters embedded into photonic resonators as well as classical emitters integrated in perovskite-based optoelectronic devices.